Mobile Mammography Screening as an Opportunity to Increase Access of Rural Women to Breast Cancer Research Studies. (September 2019) - McElfish, Pearl A; Su, L Joseph; Lee, Jeanette Y; Runnells, Gail; Henry-Tillman, Ronda; Kadlubar, Susan A
Objectives: Rural women are underrepresented in cancer research. We hypothesized that providing access to a research study to rural, medically underserved women who were receiving their breast cancer screening using a mobile mammography unit would increase the representation of rural women in a cancer cohort study. Design: This study is a cross-sectional study using a cohort of women who have been recruited to a breast cancer study in Arkansas. Setting: Recruiters accompanied a mobile mammography unit, the MammoVan, to implement a novel method for reaching and recruiting underrepresented rural Arkansas women into the study. Participants include 5850 women recruited from 2010 through 2012 as part of the Arkansas Rural Community Health (ARCH) study. Results: Participants recruited during their mammography screening on the MammoVan tended to be more rural, less educated, and more likely to be non-Hispanic than those recruited in other venues. A significant difference was not noted for race or age. Conclusion: Collaboration with the MammoVan greatly aided the recruitment of rural participants. These strategies can facilitate the representation of this historically underserved and understudied rural population in future research studies.